Impaired non-specific suppressor-inducer T-cell activity in aged murine Peyer's patches, which can be corrected largely by IL-2 in vitro. - Kawanishi, H (1989)
To shed further light on the mechanism of age-associated T-cell-mediated immunoregulatory alterations in gut non-specific mucosal immune responses, we studied in vitro the function of a variety of concanavalin A (Con A)-activated immunoregulatory T-cell subsets derived from aged murine Peyer's patches (PP) (BALB/c > 24 months old) in the production of class-specific immunoglobulins (Ig) by young (5-8 months old) lipopolysaccharide (LPS)-activated PP B cells. The in vitro induction of Con A-activated PP helper (Th) [L3T4+ Lyt-2- Vicia villosa non-adherent (VV-)], suppressor (Ts) L3T4- Lyt-2+ (VV-), and contrasuppresor (Tcs) (L3T4+ Lyt-2- VV+) T cells were compared for the two age groups. The activities of aged PP-derived Ts and Tcs cells were greatly impaired, in contrast to minor defects in activity of the aged Th cells. The induction of effector Tcs cells, however, depended on the presence of functionally effective Ts cells. Recombinant IL-2 (rIL-2) could largely correct this impaired generation of aged Ts and Tcs cells. Next, we determined the activities of Ts inducer (Tsi) (L3T4+ Lyt-2- VV-) T cells in aged PP in vitro. The cell activity was considerably diminished in aged mice. Then, we tested in vitro whether rIL-2 could reconstitute the impaired generation of the aged non-specific Tsi cell. The function of the latter cell was largely restored by rIL-2. Thus, the major functional (intrinsic) defect present in immunocompetent T lymphocytes of murine aged PP was confined to the Tsi cell.